2021
DOI: 10.2196/23771
|View full text |Cite
|
Sign up to set email alerts
|

Technology Enabled Clinical Care (TECC): Protocol for a Prospective Longitudinal Cohort Study of Smartphone-Augmented Mental Health Treatment

Abstract: Background Even before COVID-19, there has been an urgent need to expand access to and quality of mental health care. This paper introduces an 8-week treatment protocol to realize that vision—Technology Enabled Clinical Care (TECC). TECC offers innovation in clinical assessment, monitoring, and interventions for mental health. TECC uses the mindLAMP app to enable digital phenotyping, clinical communication, and smartphone-based exercises that will augment in-person or telehealth virtual visits. TEC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…While the studies differed in their clinical populations (patients with schizophrenia or depression/anxiety; college students with stress/anxiety), they all collected two common digital phenotyping data streams: geolocation (GPS) and accelerometer data. Each study presented participants with a symptom survey at least every 3 days 12–16. All participants in each study (including those who were discontinued for non-adherence to protocol) were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the studies differed in their clinical populations (patients with schizophrenia or depression/anxiety; college students with stress/anxiety), they all collected two common digital phenotyping data streams: geolocation (GPS) and accelerometer data. Each study presented participants with a symptom survey at least every 3 days 12–16. All participants in each study (including those who were discontinued for non-adherence to protocol) were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Each study presented participants with a symptom survey at least every 3 days. [12][13][14][15][16] All participants in each study (including those who were discontinued for nonadherence to protocol) were included in this analysis. Study details can be found in table 1.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…While the studies differed in their clinical populations (patients with schizophrenia; college students with stress, anxiety, and depression; patients with depression using mindLAMP to augment therapy), they all collected two common digital phenotyping data streams: geolocation and accelerometer data. Each study presented participants with a symptom survey at least every three days [13][14][15][16] . For completeness, all participants in each study (including those that were discontinued because of non-adherence to protocol) were included in this analysis.…”
Section: Data Setsmentioning
confidence: 99%
“…They have potential to increase access to care, and can provide a low-cost intervention with little staff training or presence required, increasing access to those geographically isolated. It has been proposed that apps could help redress ethnic disparities in the uptake of mental health services, as well as reduce stigma of accessing mental health services (Rauseo-Ricupero 2021). Novel apps for nursing staff can allow them to record observations and physical health monitoring data, food and fluid charts and sleep charts, minimising time spent in front of computers and taking better advantage of the capabilities of the tablet computers already available on the wards.…”
Section: Mobile Health (Mhealth) Digital Applications (Apps)mentioning
confidence: 99%